2016
DOI: 10.1080/10926771.2016.1210270
|View full text |Cite
|
Sign up to set email alerts
|

Familial Influences on Dating Violence Victimization Among Latino Youth

Abstract: Despite theoretical and empirical evidence suggesting that the family environment plays a central role in Latino youth development, relatively little is known about how family processes influence dating violence victimization among Latino adolescents. To address this gap in the literature, we used data from 210 Latino parents and their 13- to 15-year-old adolescents to examine associations between several different family processes, including both parenting practices (parent monitoring, parent–adolescent commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Prevalence rates of physical TDV specifically for Latino/a adolescents are dissimilar as well. Due to differences in sampling methods, rates for Latino/a youth range between 5% and 44% [16][17][18][19][20]. A national study on Latino youth conducted by Cuevas, Sabina, and Bell (2014) found that TDV increases with age (at around 14 years), with boys more likely to experience violence (18.35%) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence rates of physical TDV specifically for Latino/a adolescents are dissimilar as well. Due to differences in sampling methods, rates for Latino/a youth range between 5% and 44% [16][17][18][19][20]. A national study on Latino youth conducted by Cuevas, Sabina, and Bell (2014) found that TDV increases with age (at around 14 years), with boys more likely to experience violence (18.35%) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study that modeled growth curves over 10 years found the referent and supportive dimensions of familism to be significantly related to lower levels of depression among Mexican-origin families (Zeiders et al, 2013). However, research specific to familism and family violence is very limited and most evidence comes from related constructs such parental monitoring, family connectedness, family cohesion, and communication with parents (East & Hokoda, 2015;Kast et al, 2016;McNaughton Reyes et al, 2016;Yan et al, 2010). Nonetheless, some studies (Alcalde, 2010;Welland & Ribner, 2008) have reported that familism may contribute to domestic violence among Latinos as the family unity is kept at the expense of the victim's own "safety or well-being" (Welland & Ribner, 2008, p. 59).…”
Section: Familismmentioning
confidence: 99%